Peran Syekh Nawawi Al-Bantani dalam Meneguhkan Identitas Kebhinekaan Bangsa Indonesia - Muhammad War'i; Muhamad Agus Mushodiq (KURAS Institute, 2022)
Indonesia as a multi-religious and multi-cultural country requires a tolerant paradigm in an effort to maintain peace and national unity. One of the thinkers of the Indonesian nation who tends to be inclusive in seeing differences (diversity) is Sheikh Nawawi Al-Bantani. Through the principles and paradigms of writing his works, he builds a paradigm that is tolerant and caring for others and accepts the progress of the times. This paper aims to analyze the paradigm of Sheikh Nawawi regarding diversity in his works. The type of research used is qualitative with a descriptive-interpretative analysis model. The data was obtained from written documents in the form of books by Sheikh Nawawi. The results found are that Syekh Nawawi is an Islamic Nusantara figure who cares about Indonesian society, and has a high tolerance and inclusive attitude. Such a paradigm is very much needed in maintaining the existence of the Indonesian nation which is full of diversity. The existence of a scientific genealogical relationship between Sheikh Nawawi and Islamic thinkers of the Nusantara is a strong reason that his role in building the identity of the Indonesian nation is quite significant in order to maintain the integrity of the nation.